IRF4 Has a Unique Role in Early B Cell Development and Acts Prior to CD21 Expression to Control Marginal Zone B Cell Numbers - Ottens, Kristina; Satterthwaite, Anne B. (Frontiers in Immunology, 2021)
Strict control of B lymphocyte development is required for the ability to mount humoral immune responses to diverse foreign antigens while remaining self-tolerant. In the bone marrow, B lineage cells transit through several developmental stages in which they assemble a functional B cell receptor in a stepwise manner. The immunoglobulin heavy chain gene is rearranged at the pro-B stage. At the large pre-B stage, cells with a functional heavy chain expand in response to signals from IL-7 and the pre-BCR. Cells then cease proliferation at the small pre-B stage and rearrange the immunoglobulin light chain gene. The fully formed BCR is subsequently expressed on the surface of immature B cells and autoreactive cells are culled by central tolerance mechanisms. Once in the periphery, transitional B cells develop into mature B cell subsets such as marginal zone and follicular B cells. These developmental processes are controlled by transcription factor networks, central to which are IRF4 and IRF8. These were thought to act redundantly during B cell development in the bone marrow, with their functions diverging in the periphery where IRF4 limits the number of marginal zone B cells and is required for germinal center responses and plasma cell differentiation. Because of IRF4’s unique role in mature B cells, we hypothesized that it may also have functions earlier in B cell development that cannot be compensated for by IRF8. Indeed, we find that IRF4 has a unique role in upregulating the pre-B cell marker CD25, limiting IL-7 responsiveness, and promoting migration to CXCR4 such that IRF4-deficient mice have a partial block at the pre-B cell stage. We also find that IRF4 acts in early transitional B cells to restrict marginal zone B cell development, as deletion of IRF4 in mature B cells with CD21-cre impairs plasma cell differentiation but has no effect on marginal zone B cell numbers. These studies highlight IRF4 as the dominant IRF family member in early B lymphopoiesis.